THE URGENCY OF ESTABLISHING A TRUTH AND RECONCILIATION COMMISSION FOR THE SETTLEMENT OF HUMAN RIGHTS VIOLATIONS IN PAPUA FROM THE PERSPECTIVE OF SPECIAL AUTONOMY FOR PAPUA - Sri Handayani Retna Wardani, Nidya Tajsgoani, Endang Sulistyaningsih, (Jurnal Meta-Yuridis, 2024)
AbstractPapua's Special Autonomy provides a legal basis for addressing conflicts and human rights violations through non-judicial mechanisms that are more inclusive and in accordance with the sociocultural context of the local community. Â In its fourth report covering the period April 2013 to December 2014, the International Coalition for Papua (1CP) documented 653 arrests resulting from 46 separate incidents. The human rights situation in Papua is worsening, as human rights violations and abuses continue to occur. Many organisations advocate for the protection of human rights in Papua; however, these efforts to defend and promote human rights are often unrecognised or poorly received. The research method used in this research is normative legal research method, using statutory approach, conceptual approach, and comparative approach.This study discusses the ratio legis of the Papua Special Autonomy Law regarding the establishment of a TRC (Truth and Reconciliation Commission) based on several main reasons: first, the TRC allows for a more comprehensive and fair settlement compared to formal legal channels; second, the TRC respects local wisdom in the reconciliation process; third, this institution plays an important role in rebuilding trust between the Papuan people and the central government; and fourth, the TRC is expected to prevent the recurrence of human rights violations in the future and support long-term peace in Papua. In addition, the TRC is an important step towards respecting the rights of the Papuan people, improving relations between conflicting parties, and strengthening the implementation of a fair and inclusive Special Autonomy. The problems of resolving human rights violations in Papua from the perspective of Special Autonomy reflect complex challenges that require comprehensive attention. Although the Papua Special Autonomy Law provides a legal basis for dealing with human rights violations in an inclusive and peaceful manner, its implementation is far from optimal. This is due to several factors, such as slow implementation, overlapping authority between the central and local governments, and counterproductive militaristic approaches. The Papuan people's lack of trust in the government, both central and local, as well as victims' limited access to justice and redress, exacerbate this problem.Â Keywords: TRC, special autonomy, Human Rights